Broadband Surface-Wave Antenna With a Novel Nonuniform Tapered Metasurface - Feng, Guirong; Chen, Lei; Xue, Xingsi; Shi, Xiaowei (IEEE antennas and wireless propagation letters, 2017)
A broadband surface-wave antenna with a monopole-like radiation pattern is presented. The antenna provides a wide bandwidth by two techniques, including the utilization of a novel nonuniform tapered metasurface that has smaller inner rectangular patches for exciting two resonant modes of TM 01 and TM 02 simultaneously, and a reduction of ground-plane size for constructively increasing surface-wave fields. The measured results show that the proposed antenna achieves a wide bandwidth of 33.1% (4.56-6.37 GHz) for a low profile of about 0.06 λ 0 and has an average gain of 6.34 dBi.